Inhibitory Effects of a Novel PPAR-γ Agonist MEKT1 on Pomc Expression/ACTH Secretion in AtT20 Cells - Rehana Parvin; Erika Noro; Akiko Saito-Hakoda; Hiroki Shimada; Susumu Suzuki; Kyoko Shimizu; Hiroyuki Miyachi; Atsushi Yokoyama; Akira Sugawara (PPAR Research)
Although therapeutic effects of the peroxisome proliferator-activated receptor gamma (PPAR-γ) agonists rosiglitazone and pioglitazone against Cushing’s disease have been reported, their effects are still controversial and inconsistent. We therefore examined the effects of a novel PPAR-γ agonist, MEKT1, on Pomc expression/ACTH secretion using murine corticotroph-derived AtT20 cells and compared its effects with those of rosiglitazone and pioglitazone. AtT20 cells were treated with either 1 nM~10 μM MEKT1, rosiglitazone, or pioglitazone for 24 hours. Thereafter, their effects on proopiomelanocortin gene (Pomc) mRNA expression were studied by qPCR and the Pomc promoter (−703/+58) activity was demonstrated by luciferase assay. Pomc mRNA expression and promoter activity were significantly inhibited by MEKT1 at 10 μM compared to rosiglitazone and pioglitazone. SiRNA-mediated PPAR-γ knockdown significantly abrogated MEKT1-mediated Pomc mRNA suppression. ACTH secretion from AtT20 cells was also significantly inhibited by MEKT1. Deletion/point mutant analyses of Pomc promoter indicated that the MEKT1-mediated suppression was mediated via NurRE, TpitRE, and NBRE at −404/-383, −316/-309, and −69/-63, respectively. Moreover, MEKT1 significantly suppressed Nur77, Nurr1, and Tpit mRNA expression. MEKT1 also was demonstrated to inhibit the protein-DNA interaction of Nur77/Nurr1-NurRE, Tpit-TpitRE, and Nur77-NBRE by ChIP assay. Taken together, it is suggested that MEKT1 could be a novel therapeutic medication for Cushing’s disease.